Pengaruh Love of money dan Financial distress terhadap Kepatuhan Pajak UMKM: Moderasi Pemeriksaan Pajak - Nauticia Endita Digtama Putri; Alif Faruqi Febri Yanto (Owner : Riset dan Jurnal Akuntansi, 2026)
Malang City is one of the regions experiencing MSME tax non-compliance, as reflected in various cases such as tax arrears, “ghosting” restaurants, manipulation of the e-tax system, and engineered turnover reporting to reduce tax burdens. This study aims to examine the effect of love of money and financial distress on tax compliance among MSME taxpayers, as well as to analyze the moderating role of tax audits in these relationships. The population of this study consists of MSMEs registered as taxpayers in Malang City. This study employs a non-probability sampling technique using purposive sampling with specific criteria, resulting in a minimum sample of 115 respondents. Primary data were collected through structured questionnaires using a Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS to evaluate both direct and moderating effects. The results indicate that love of money has a negative and significant effect on tax compliance. Financial distress also negatively and significantly affects tax compliance. However, tax audits are not able to moderate the relationship between love of money and tax compliance, nor between financial distress and tax compliance. This study concludes that internal psychological and financial factors play an important role in influencing MSME tax compliance, while tax audits have not been effective in moderating these relationships. This study highlights the dominant role of internal factors in MSME tax compliance and the limited effectiveness of tax audits, emphasizing the need for behavioral approaches, education, and financial support policies.